A Photoactivatable Innate Immune Receptor for Optogenetic Inflammation - Moser, Brittany A. (ACS Chem Biol, 2016)
Although spatial and temporal elements of immune activation mediate the intensity of the immune response, few tools exist to directly examine these effects. To elucidate the spatiotemporal aspects of innate immune responses, we designed an optogenetic pattern recognition receptor that activates in response to blue light. We demonstrate direct receptor activation, leading to spatial and temporal control of downstream signaling pathways in a variety of relevant cell types. We combined our platform with Bi-molecular Fluorescence Complementation (BiFC), resulting in selective fluorescent labeling of cells in which receptor activation has occurred.